Spatial variation of microbial communities in sediments along the environmental gradients from Xiaoqing River to Laizhou Bay. Issue 1 (15th July 2017) - Yu, Shu-Xian; Pang, Yun-Long; Wang, Yin-Chu; Li, Jia-Lin; Qin, Song
Abstract: The Laizhou Bay is famous for aquaculture, but has been subject to eutrophication and contamination for years. High concentrations of nutrients from the Xiaoqing River are considered as the main cause for significant eutrophication in the west of Laizhou Bay. Here we present results of the research on sedimentary microbial assemblages along this spatial gradient between riverine and marine environments by high-throughput sequencing. The predominant phyla/classes of bacteria and fungi clustered the samples into two distinct provinces, while discriminant taxa of each province were strongly associated with spatial factors and inorganic nitrogen. Spatial variation of bacterial communities was mainly related with the distribution of phosphates, suggesting a phosphate-limitation pattern for the bacterial communities. Alpha- and beta-diversity of fungal communities exhibited a significant correlation with water depth. We consider the distinct distributional gradients of bacterial and fungal communities partly explain the different roles in the biogeochemical processes of coastal sediment. Highlights: Discriminant taxa strongly related with spatial factors and inorganic nitrogen. Bacterial biogeography suggested a phosphate-limit pattern. Fungal diversity exhibited significant correlations with water depth.